Carbon sequestration potential of Alnus nepalensis in the mid hill of Nepal: A case study from Kaski district - Ranabhat, S; Awasthi, KD; Malla, R (Banko Janakari, 2009)
This study was carried out to analyze the carbon content in different parts of Alnus nepalensis, and to assess the effect of aspect and altitude in the carbon storage in Alnus nepalensis as well as to quantify the total carbon sequestration (stock) in Alnus nepalensis forest in the mid-hills of Kaski District. The inventory for estimating above and below ground biomass of forest was carried out using stratified random sampling technique. The carbon content in different parts of Alnus nepalensis was quantified using combustion method in the laboratory. For determining the soil carbon content, six soil profiles from each aspect were excavated and soil samples were taken from soil profile up to 1 m depth for deep soil and up to bedrock for shallow soils at the interval of 20 cm. Mean carbon content in stem, branches, leaves and bark of Alnus nepalensis were found to be 40.52%, 33%, 9.56% and 16.4%, respectively. Total biomass carbon sequestered in northern aspect was 30.20 t/ha while for southern aspect it was 39.00 t/ha. In both the aspects higher carbon sequestration was observed at an elevation range of 1200-1300m i.e. 34.8 t/ha and 45.6 t/ha in northern and southern aspects, respectively. Soil carbon sequestration in northern and southern aspects was found to be 113.4 t/ha and 169.30 t/ ha, respectively. The total carbon sequestration potential of Alnus nepalensis forest was estimated to be 186.05 t/ha. Key words: Alnus nepalensis, altitude, aspect, carbon sequestration, mid hills doi: 10.3126/banko.v18i2.2167 Banko Janakari, Vol. 18, No. 2, 3-9